Factores predictivos de apendicitis perforada en pacientes intervenidos quirúrgicamente en el Hospital Regional de Loreto 2022 - Garay Tuanama, Sharon Kristell (2022)
Abdominal pain syndrome constitutes up to 10% of all emergency department visits. Within surgical emergencies with abdominal focus, acute appendicitis is considered the most frequent in emergency and urgent areas of hospital services. Perforated appendicitis is clearly associated with more mortality and morbidity than non-perforated appendicitis. Mortality in non-gangrenous appendicitis is close to 0.1%, in gangrenous 0.6% and in appendiceal perforation the risk of dying approaches up to 5%. Defining risk factors has an impact not only on the early approach with a reduction in intra- and postoperative complications, but also has its main purpose in reducing mortality. Several factors have been evidenced in the medical literature, highlighting potential factors such as age, sex, laboratory and radiological findings. Male sex, advanced age, elevation of C-reactive protein, bilirubin and neutrophil/lymphocyte radius, as well as delay in the start of surgery are some of the factors that have been demonstrated in various studies. Our study aims to determine what are the predictive factors of perforated appendicitis in patients with acute appendicitis in our Regional Hospital of Loreto. For this reason we developed a type of Analytical research with a Population and study sample: taking into account all patients over 1 year admitted to the emergency room with clinical suspicion of acute appendicitis and subsequently confirmed intraoperatively in the operating room of our Regional Hospital of Loreto during the year 2022. Acute appendicitis is therefore a common phenomenon in emergency services throughout the health system. Our Regional Hospital of Loreto is not exempt from this reality. Appendicitis has been recognized as the most frequent cause of intra-abdominal sepsis, this in any age range carries a higher risk of mortality. Consequently, sociodemographic factors and laboratory findings are predictive factors of perforated appendicitis in patients with acute appendicitis at the Regional Hospital of Loreto.This brings with it objectives and results that improve our information system with well-designed and protocolized studies and perhaps most importantly: improve the quality of care, the optimization of interventions and the reduction of morbidity and mortality due to perforated appendicitis. This study aims to be one of the first investigations with good methodological support addressing a frequent pathology, from which relevant, current and research-promoting information can be obtained in the surgical field.